Paisagem e literatura na geografia : diálogos a partir do legado de Eidorfe Moreira (1912-1989) - Pacheco, Nathalia Costadelle (2022)
This work seeks to present the thought of Eidorfe Moreira (1912-1989) and his contributions to the geographic science of the 20th century, observing his references, from the centrality of the concept of landscape and its dialogue with literature. This dissertation prioritizes whose themes that deal with epistemic questions in geographhy, with the intention of deconstructing the regionalist image that intellectuals who write from outside the renowned academic institutions, national and international, have. Regarding the epistemological content, Moreira reveals a unique and innovative perspective for Geography developed from the second half of the 20th century, resuming sensitive elements from a Classical Geography, however organizing his own conceptions in dealing with the geographical landscape. It is on this dimension of his work that we dedicate ourselves in this research. Among these paths and dialogues, we think about the valorization of artistic manifestations, aesthetic experiences and knowledge that were not always considered in the conventional academic environment, allied to the teaching of Geography from the concept of landscape. Keeping the minimum conditions for the teaching-learning practice, Geography and Literature can awaken the primordial sensitivity for the construction of another relationship with nature.